Resources of emotional resilience and its mediating role in teachers’ well-being and intention to leave - Bagdžiūnienė, Dalia; Kazlauskienė, Aušra; Nasvytienė, Dalia; Sakadolskis, Emilija (Frontiers in Psychology, 2023)
The continuing attention of scholars and practitioners to the teaching profession, teachers and teaching is based above all on the fact that societal progress is impossible without an effective education system. Teachers are the "soft" dynamic, and at the same time, a driving force in this constantly changing system, and research into the prerequisites for their effective performance requires constant attention. In this study, the main phenomenon under analysis is the emotional resilience of teachers-the internal capacity to adapt, manage or cope with emotionally demanding situations. The purpose was to investigate work-related and personal resources that contribute to teachers' emotional resilience and its role in the links between resources, teacher well-being, and the intention to leave. Data were collected using convenience sampling and included 522 teachers working in Lithuanian primary and secondary schools. An online self-administered questionnaire consisted of scales that assessed teachers' job resources, self-efficacy, well-being, and intention to leave. The research revealed that perceived workplace characteristics -performance feedback, autonomy, social support, and opportunities for professional growth-along with self-efficacy were positively related and predicted teacher emotional resilience. Emotional resilience was found to be a direct positive predictor of teacher well-being along with job resources and self-efficacy and have a mediating effect on the relationships between work-related resources and self-efficacy as independent variables and teacher wellbeing as a dependent variable. Contrary to well-being is teachers' intention to leave a school, which is usually an undesirable outcome for an organization. The study revealed that this intention is negatively affected by job resources and self-efficacy, however emotional resilience did not impact teachers' intention to quit. Based on the results, the article outlines avenues for further research and provides implications for strengthening teachers' emotional resilienceThe study revealed that this intention is negatively affected by job resources and self-efficacy, however emotional resilience did not impact teachers' intention to quit. Based on the results, the article outlines avenues for further research and provides implications for strengthening teachers' emotional resilience.